THERMODYNAMIC OF Mg(II), Cd(II), AND Ni(II) ADSORPTION ON SULFONIC MODIFIED SILICA GEL - Choiril Azmiyawati; Nuryono Nuryono; Narsito Narsito (Indonesian Journal of Chemistry, 2005)
Silica gel modified with 4-amino-5-hydroxy-2,7-naphtalenedisulphonate (SG-SO3-) has been applied for adsorption of Mg(II), Cd(II), and Ni(II) in aqueous medium. In addition, three thermodynamic parameters i.e. capacity, adsorption constant and energy of adsorption were calculated. Adsorption was conducted in a batch system and metal ion remaining in the solution was determined by atomic adsorption spectrophotometry (AAS). The amount of adsorbed metal ions was calculated from the difference of metal ion concentration before and after interaction. Adsorption parameters i.e. capacity (ns2), constant (b), and energy (E) of adsorption were calculated using the equation of Langmuir isotherm. Results showed that ns2 for Mg(II), Cd(II), and Ni(II) on the adsorbent were 4.67 x 10-4, 1.19 x 10-4, and 0.13 x 10-4mol g-1, respectively. The values of b for Mg(II), Cd(II), and Ni(II) were 49.35 x 105, 173.46 x 105, and 181.12 x 105 g-1, respectively. Furthermore, it was found that E for all metal ion investigated was in the range of 26-30 kJ/mol, indicating the involvement of chemical adsorption.